1987
DOI: 10.1071/pp9870689
|View full text |Cite
|
Sign up to set email alerts
|

Shoot Control of Supernodulation in a Number of Mutant Soybeans, Glycine max (L.) Merr

Abstract: Seven supernodulation mutants of soybean (Glycine max) derived from the cultivar Bragg were investigated for shoot control of the supernodulation response. Reciprocal grafts showed that supernodulation in all lines tested was obtained only if the genotype of the shoot was homozygous for the mutant allele(s). In addition two lines of Korean origin (selected in the field for increased nitrate tolerance) were included in the grafting studies. Under our experimental conditions nitrate tolerance could not be demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
25
0

Year Published

1993
1993
2003
2003

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 0 publications
1
25
0
Order By: Relevance
“…Grafting experiments with legumes have shown that there is a shoot factor involved in autoregulation that is active even across species boundaries (Delves et al, 1987a(Delves et al, , 1987b. Thus, it is likely that the translocatable signal formed in roots affects the production of a translocatable shoot factor that controls nodule number (Caetano-Anollés and Gresshoff, 1991).…”
Section: Regulation Of Nodule Numbermentioning
confidence: 99%
“…Grafting experiments with legumes have shown that there is a shoot factor involved in autoregulation that is active even across species boundaries (Delves et al, 1987a(Delves et al, , 1987b. Thus, it is likely that the translocatable signal formed in roots affects the production of a translocatable shoot factor that controls nodule number (Caetano-Anollés and Gresshoff, 1991).…”
Section: Regulation Of Nodule Numbermentioning
confidence: 99%
“…The biochemical nature, the biosynthetic site(s), and the pathway by which the signals are transported and function are unknown. Wedgegrafting studies with most legume nodulation mutants and their respective wild-type parents have demonstrated that it is the shoot that determines the root nodulation phenotype, which suggests that the shoot is the source of the proposed SDI (Delves et al, 1986(Delves et al, , 1987Gremaud and Harper, 1989;Francisco and Akao, 1993;Hamaguchi et al, 1993). Recently, by wedge-and approach-grafting with different shoots (with or without cotyledons and with or without primary leaves) and by nodulation of rooted leaf cuttings, Francisco and Harper (199513) clearly demonstrated that the leaf autoregulates the number of nodules in soybean plants, which confirmed a report by Delves et al (1992).…”
mentioning
confidence: 99%
“…One must keep in mind that much of our knowledge of legume nodule autoregulation is based on the comparative studies of wild-type and hypernodulating or supernodulating mutants (Delves et al, 1986(Delves et al, , 1987(Delves et al, , 1992CaetanoAnolles andGresshoff, 1990, 1991a;Francisco and Akao, 1993;Francisco and Harper, 1995b). It is possible that the hypernodulating or supernodulating mutants have been chemically altered in a biosynthetic step associated with the production of a "common" hormonal compound rather than the proposed nodulation-specific signal.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is assumed that in these hypernodulating mutants there is a lack of or decrease in the autoregulatory control of nodulation which restricts the nodule number followed by the nodule primordial initiation after infection with Bradyrhizobia. Several reciprocal grafting experiments (Delves et al 1987;Barbera and Harper 1993) and a hypernodulation trait in a rooted single-leaf of mutant lines revealed that the shoot organs especially mature leaves, and not the roots or apical shoots, regulate the nodule number.…”
mentioning
confidence: 99%